Assessing liver disease in HIV–HCV coinfected patients. Issue 5 (September 2015) - Tsochatzis, Emmanuel A.; Castera, Laurent
<x xml:space="preserve">Abstract</x> Purpose of review It is estimated that up to 10% of patients with HIV have chronic hepatitis C (HCV)–HIV coinfection in the Western world. Assessment of liver disease is essential in such patients in order to diagnose cirrhosis at an early stage, prioritize for anti-HCV treatment but also assess fibrosis regression after sustained viral response (SVR). In this review, we present a critical appraisal of liver disease assessment in patients with HIV–HCV co-infection. Recent findings Liver biopsy has largely been replaced by noninvasive fibrosis assessment in most coinfected patients, although it is still of value if there are concerns of additional diagnoses. Noninvasive assessment includes serum markers and liver stiffness measurement using elastography-based techniques. Certain serum markers, such as FIB-4, SHASTA index, and Fibrometer HIVC have been specifically developed in patients with HIV–HCV coinfection. Transient elastography has advantages over serum markers, as it is not influenced by concomitant antiretroviral medication, HIV replication, CD4 cell count, or nonliver inflammatory processes. Summary Noninvasive markers are increasingly used for clinical decision-making and predicting clinical outcomes in HIV–HCV coinfected patients. The concept of residual risk for liver-related events after SVR needs to be further explored with noninvasive fibrosis tools in prospective studies.